Tragedy of the commons in ecotourism: A case study at Kenyir Lake, Malaysia - Che Jamil, Mohd Fitri; Yusof, Nor’Aini (2013)
Tourism is the only sector in which natural environment plays a substantial role. Nowadays, the interaction between ecotourism and the natural environment is generally inter-dependence; ecotourism holds on to natural environment for resources, and in order to survive the environmental threat, natural environment in turn, depends on ecotourism. In human society, the selfish use of common resources can lead to catastrophic consequences, a situation known as the ‘tragedy of the commons’ (TOC). More often than not, natural environment as the common pool resource (CPR) is overused and degraded, as is the unfortunate fate of most TOC. Thus, this paper explains this particular circumstance in the context of Ecotourism in Malaysia, specifically in Kenyir Lake. First, it introduces and details the TOC. before exploring the possibility of Kenyir Lake being a CPR issue. Finally, this paper attempts to add an ethical dimension (also known as Environmental Culture) into the debate on the interaction between tourism and CPRs based on findings established on Kenyir Lake.